Top-Class Sports - Grigoryeva, Elena (project baikal, 2017)
The universe unites us all Through the summer religion called football And the winter one called hockey. Robert Rozhdestvensky The top-class sports are rich in great events. The most serious challenge in front of today’s Russian sports and architecture community is, certainly, the World Football Championship. Russia is preparing stadiums for the World Football Championship in the both capitals and the regional centers: Samara, Volgograd, Nizhny Novgorod, Sochi, Yekaterinburg, Rostov and Kaliningrad. The landmark structures demand from architects deep investigation of technologies and compliance with strict Russian and FIFA standards. Will such a large-scale construction be helpful in revitalization of Russian football? Let’s hope so. But large-scale sporting events take place not only in the cities of the World Football Cup. For example, the opening of the Krasnodar Stadium is gathering much praise now (the Allianz Arena is no match for it). Siberia does not stand aside. The old stadium in Irkutsk has housed the World Ball Hockey Championship, and the Metkii Billiard Club (where architects and builders have recently competed for the “Brick in Irkutsk” Prize) has housed the Russian Championship. However, Krasnoyarsk has beaten other cities by winning the right to host the 2019 Winter Universiade.